Komunikacja rodzic-nauczyciel podczas nauczania zdalnego w szkole specjalnej - Łukaszczyk-Cibiorz, Jasmina (Zeszyty Naukowe Pedagogiki Specjalnej, 2022)
The article presents the importance of communication in cooperation between the teacher and parents in the context of children attending special schools, two different perspectives of communication problems during distance learning, summary of the negative effects of distance learning and new solutions that have been invente over time.